Entrepreneurial self-efficacy and entrepreneurial intention among Polytechnic students involved in entrepreneurship education / Norasmah Othman … [et al.] - Othman, Norasmah; Mohd Hisam, Nur Sa’adah; Radin A Rahman, Radin Siti Aishah; Sahid, Sheerad (Faculty of Accountancy, 2019)
Entrepreneurship, as a field, is being focused on by all educational institutions, including polytechnic institutions. Various plans and strategies have been designed to encourage the involvement of students in entrepreneurship. Until now, it has been reported that students’ participation in entrepreneurship, particularly that of polytechnic students, is less than satisfactory. This study aims to identify the entrepreneurial self-efficacy and entrepreneurial intentions of polytechnic students who have been actively involved in entrepreneurship education programs, compared with those who have never had any similar involvement. This study used a survey questionnaire, which was sent to a randomly selected group of 317 polytechnic students across Malaysia. Responses were analyzed using descriptive and inferential statistical methods to establish correlations between variables. Results show that students who have been involved in entrepreneurship courses have a higher level of entrepreneurial self-efficacy compared to students who have never received entrepreneurship education. However, the level of entrepreneurial intention is high regardless of involvement in entrepreneurship education. Furthermore, there is no significant difference in the level of entrepreneurial self-efficacy between the two groups. There is a significant positive correlation between a student’s entrepreneurial self-efficacy and entrepreneurial intention after graduating from a polytechnic institution in Malaysia. The findings can serve as a guideline for policy makers, curriculum developers, and polytechnic educators to improve existing plans and strategies so that they are more relevant to current needs.